Ketahanan Dan Keberlangsungan Usaha Melalui Tertib Pembukuan Bagi Pelaku UMKM - muhammad rimawan (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
Bookkeeping training for MSMEs in the Ntobo Village area aims to improve the ability of MSMEs to manage their business finances. The method used for this community service activity is by providing a training in making bookkeeping and the material provided consists of modules adapted from MSME financial accounting guidelines. The activity was carried out for 1 day at the location of each MSME. The results of this activity show that the majority of participants understand the importance of bookkeeping to manage their business finances and are able to implement simple bookkeeping for their business. As a result of the training, MSME actors are able tokeep simple bookkeeping that allows them to measure their business performance and make decisions for better business ventures in the future. This training is expected to provide support for local economic growth through improving the quality of MSME financial management in the Ntobo Village